Faktor-Faktor yang Memengaruhi Ketahanan Hidup Pasien HIV/AIDS: A review - atmojo, joko tri; Maylanda, Vivi Erlina; Prastiwi, Aprilia Tina; Darmayanti, Aquartuti Tri; Kuntari, Saras (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2019)
Until now there is no vaccine that can fight HIV / AIDS. Antiretroviral Agents (ARVs) can only provide survival by slowing the reproduction of viruses. The purpose of this review is to describe the factors that can affect survival (PLWHA) after ARV administration. factors that can affect the survival / survival of people with HIV / AIDS (PLWHA) in addition to the provision of antiretroviral drugs. This review was conducted by the author in January - March 2019, by searching databases including PubMed, Google scholar, and open access science direct. In this review, it has been explained various factors that affect the survival of PLWHA who receive ARV treatment, including: Birth sex, age, nutritional status, CD4 levels and co-infection.